Investigation of the failure in a pipe of produced water from an oil separator due to internal localized corrosion. (March 2016) - Tavares, S.S.M.; Pardal, J.M.; Mainier, F.B.; da Igreja, H.R.; Barbosa, E.S.; Rodrigues, C.R.; Barbosa, C.; Pardal, J.P.
Abstract: This work aims to analyze the failure in a pipe of produced water in an oil crude primary separation system. The produced water commonly has a high concentration of soluble salts and sediments. This fluid, which can be discarded or reused, is usually transported by seamless pipes of low carbon steel. In this case, the pipe employed was built by electric resistance welding (ERW) process. The sediment deposits and the elevated Cl − concentration in the produced water promoted the failure by localized corrosion through the longitudinal weld of the pipe. The chemical composition of the pipe, and its high level of inclusions contributed to the premature failure in operation. Thus, some recommendations were presented to mitigate premature failures in this type of application. Highlights: Analysis of a failure by corrosion in a steel pipe for water from an oil separator The internal corrosion was mainly caused by Cl − and S present in the produced water. The bottom of the pipe suffered more corrosion due to differential aeration effect. Pearlite suffered preferential attack. The pipe material and fabrication process favored the premature failure.